Oxidative metabolism altered by plant growth regulators in atemoia seeds (Annona x Atemoya mabb.) ‘Thompson’ - Hata, Ana Paula Yuki [UNESP]; Ferreira, Gisela [UNESP]; Sousa, Marília Caixeta [UNESP]; Bezerra, Breno Kennedy Lima [UNESP]; Kissmann, Camila [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this work was to validate the enzymatic activity in Annona x atemoya seeds submitted to treatments with plant growth regulators belonging to the group of gibberellins and cytokinins for overcoming dormancy during the germination process. Initially, the water acquisition curve was determined, where two points of phase II (72 and 144 hours) were determined to evaluate the activity of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) enzymes in atemoya seeds after the application of two plant growth regulators. Treatments with GA resulted in higher activity of SOD enzyme, which may be favored the higher germination percentage and speed in comparison to control treatment. In cases in which SOD enzyme presented high activity, other enzymes showed the opposite, which indicates the predominantly production of superoxides during this period. The POD enzyme also has activity in seeds treated with gibberellin, which suggests interaction of ROS with GA in the process of dormancy overcoming. Treatments with cytokinin and cytokinin + gibberellin resulted in germination percentage similar to control and no activity pattern of SOD, POD and CAT enzymes that could be correlated with germination metabolism was observed.
Metabolismo oxidativo alterado por reguladores vegetais em sementes de atemoia (Annona x atemoya mabb.) ‘Thompson’
Keywords: Annonaceae; Cytokinin; Enzymatic activity; Germination; Gibberellin